A Psychological Conflict Reflected by Margaret as the Main Character on “Big Eyes” Movie: A Psychoanalytic Approach - Miftahul Jannah; Ira Maisarah (UNIB Press, 2024)
Everybody can suffer psychological conflict, whether consciously or unconsciously. It usually happens when someone faces difficulties and finds it difficult to choose among several options. Psychological conflict can also arise when a person lacks strong guiding principles. Big Eyes movie tells about psychological conflicts experienced by Margaret the main actress as a painter. Margaret faced many struggles for hiding all of her husband’s untruth. This paper analyzed psychological conflict reflected by Margaret as the main character on Big Eyes movie and Margaret‘s personality in facing her psychological conflict. The theoritical framework of analysis was Psychoanalytic approach by Sigmud Freud. Based on the result of data analysis, it was found that there were two kinds of psychological conflicts faced by the main character, Margaret, they are pressure and unconfident. Margaret got pressures from her husband because she knew everything about her husband’s popularity and his untruth. Margaret felt unconfident because she had not rational thinking. She trusted her husband’s saying too much, so her husband dominated her easily.